2017
DOI: 10.1371/journal.pone.0169543
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Assessment of the Probiotic Potential of Lactococcus lactis LMG 7930 against Ruminant Mastitis-Causing Pathogens

Abstract: Mastitis in dairy ruminants is considered to be the most expensive disease to farmers worldwide. Recently, the intramammary infusion of lactic acid bacteria has emerged as a potential new alternative to antibiotics for preventing and treating bovine mastitis. In this study we have investigated in vitro the probiotic potential of Lactococcus lactis LMG 7930, a food-grade and nisin-producing strain, against mastitis-causing pathogens. We have characterized its carbohydrate fermentation and antibiotic susceptibil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
34
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(37 citation statements)
references
References 28 publications
3
34
0
Order By: Relevance
“…Both L. brevis and L. lactis , the two most abundant bacterial species found in our FSJH preparation, are lactic acid bacteria, which are known to include many species with probiotic properties ( Ljungh and Wadstrom, 2006 ). Additionally, several lines of evidence indicate the strain-specific probiotic activities of L. lactis ( Yadav et al, 2009 ; Han et al, 2015 ; Lee et al, 2015 ; Armas et al, 2017 ; Oliveira et al, 2017 ) and L. brevis ( RönkĂ€ et al, 2003 ; Linsalata et al, 2004 ; Fukao et al, 2013 ; Waki et al, 2014 ). Moreover, for the past few years, a large number of studies have revealed the probiotic health effects of L. plantarum ( Seddik et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Both L. brevis and L. lactis , the two most abundant bacterial species found in our FSJH preparation, are lactic acid bacteria, which are known to include many species with probiotic properties ( Ljungh and Wadstrom, 2006 ). Additionally, several lines of evidence indicate the strain-specific probiotic activities of L. lactis ( Yadav et al, 2009 ; Han et al, 2015 ; Lee et al, 2015 ; Armas et al, 2017 ; Oliveira et al, 2017 ) and L. brevis ( RönkĂ€ et al, 2003 ; Linsalata et al, 2004 ; Fukao et al, 2013 ; Waki et al, 2014 ). Moreover, for the past few years, a large number of studies have revealed the probiotic health effects of L. plantarum ( Seddik et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although some approaches show great promise for future treatment methods or at least for complemental therapy, there is no contemporary alternative available for in vivo administration (Gomes & Henriques, ). Several studies investigated the application of lactic acid bacteria (LAB) as mammary probiotics to inhibit in vitro growth of MCP, prevent or compete MCP biofilm formation or reduce IMI (Armas, Camperio, & Marianelli, ; Assis et al., ; Bouchard, Rault, Berkova, Le Loir, & Even, ; Bouchard et al., ; Piccart, VĂĄsquez, Piepers, De Vliegher, & Olofsson, ).…”
Section: Alternative Therapeutic Approachesmentioning
confidence: 99%
“…Criteria used for the pre-selection of probiotic strains isolated from milk samples are the production of bacteriocins or other compounds interfering with the growth or survival of mastitis pathogens, the absence of known virulence factors or wide antibiotic resistance, and sometimes surface properties as indicators of the propensity to colonize an epithelium site ( 33 ). Probiotics used to prevent bacterial spoilage of cheese were also considered as mammary probiotic candidate and the capacity of the selected strain to adhere to and invade MECs was assessed ( 98 ).…”
Section: Appraisal Of Published Probiotic Trials In Relation To Mastimentioning
confidence: 99%